IMPLIKASI JALUR SUTRA MARITIM CINA TERHADAP PEMBANGUNAN GEOEKONOMI MARITIM INDONESIA - Rahmi Fitriyanti (Media Wawasan Ilmu Publishing, 2026)
This study aims to analyze trends, opportunities, challenges, and research gaps regarding the implications of China's Maritime Silk Road (MSR) on Indonesia's maritime geo-economic development. Employing a systematic literature review (SLR) based on the PRISMA framework for publications from 2018-2025 across Scopus, ScienceDirect, and Google Scholar, the study found a significant increase in MSR-related research concerning Indonesia since 2018, with stable publication growth and one projected study in 2025. The analysis reveals that MSR offers substantial opportunities for Indonesia, including accelerating maritime infrastructure (e.g., port and logistics investments), enhancing trade connectivity, potential foreign direct investment, and technology transfer. However, these opportunities are accompanied by significant challenges and risks such as potential debt dependency, environmental impacts from large-scale projects, issues of economic sovereignty, maritime security, and local industry competition. This study extends regional connectivity and sustainable development theories by positioning project governance and risk mitigation as crucial, complementary mechanisms within the Indonesian maritime geo-economic context. The research concludes that significant gaps remain, particularly in analyzing long-term socio-economic impacts on coastal communities, the effectiveness of national policies in balancing opportunities and risks, and inter-regional comparisons, all of which necessitate an interdisciplinary approach for robust evidence-based policy recommendations.